Trends in Students’ Mathematical Problem-Solving Skills: A Systematic Review and Bibliometric Analysis of GeoGebra-Assisted Problem-Based Learning Research (2021–2025) - Nirwana Zuhaida; Emi Pujiastuti; Zaenuri; Walid (Media Pendidikan Matematika, 2025)
Education plays a crucial role in developing high-quality human resources, and mathematics serves as a strategic discipline for strengthening logical, critical, and analytical thinking skills. One of the key competencies emphasized by the NCTM is mathematical problem-solving, which remains relatively low according to the 2022 PISA results. To address this issue, the GeoGebra-assisted Problem-Based Learning (PBL) model is applied because it fosters interactive and meaningful learning experiences. This study aims to analyze research trends and the implementation of mathematical problem-solving skills through the GeoGebra-assisted PBL model. This study employed a Systematic Literature Review (SLR) combined with bibliometric analysis using VOSviewer. A total of 200 articles were initially identified from the Google Scholar database through the Publish or Perish application (2021–2025); after applying inclusion and exclusion criteria and quality assessment procedures, 9 articles were selected for final synthesis and bibliometric mapping of keyword co-occurrence, network, and overlay visualizations. The analysis shows that the implementation of the GeoGebra-assisted PBL model consistently enhances students’ mathematical problem-solving skills. PBL cultivates critical thinking skills, while GeoGebra supports concrete visualization of mathematical concepts. The integration of both has proven effective and innovative in improving mathematics learning outcomes in the digital era.